Hypnea wynnei and Hypnea yokoyana (Cystocloniaceae, Rhodophyta), two new species revealed by a DNA barcoding survey on the Brazilian coast - Nauer, Fabio; Cassano, Valéria; Oliveira, Mariana C. (Phytotaxa, 2016)
Two new species of the red algal genus Hypnea (Gigartinales) are described for the southeastern coast of Brazil based on three molecular markers (COI-5P, rbcL and UPA), detailed morphological analysis, and comparison with closely related species. These species were named H. wynnei Nauer, Cassano & M.C. Oliveira and H. yokoyana Nauer, Cassano & M.C. Oliveira. Hypnea wynnei is characterized primarily by its reduced size, sub-erect tufts with few lateral branches and entangled basal portion, a thallus that is flattened only at the apical portions, and tetrasporangial sori developed only at apical portions of the branchlets. Hypnea yokoyana is characterized by its larger thallus, profuse branching, entirely terete axes, larger diameter of the main axes, and lack of entangling at its base. The molecular data support the conclusion that H. wynnei and H. yokoyana are distinct from other Hypnea species and are distantly related to Hypnea from the Brazilian coast.